Assessing the balance between greenhouse gases and ammonia emissions from Irish pastures amended with cattle slurry - Bourdin, Frederic (Cranfield University, 2012)
Agriculture in Ireland is the main source of ammonia (NH3) and contributes 30% of greenhouse gas emissions (GHG), with the majority of these emissions associated with livestock production. As a result, strategies promoting reductions in NH3 and GHG emissions are required. The aim of this work was: (i) to assess the impact of various NH3 abatement techniques on GHG release from a grassland soil; (ii) to investigate the consequences of organic nitrogen (N) applications in terms of carbon (C) sequestration in soils. The effects of slurry dry-matter content, application technique and timing of application were studied in a fifteen month field-plot experiment where gaseous emissions (CO2, N2O, CH4 and NH3) post-application were monitored. The natural abundance 13C tracer technique was also used to investigate the short-term dynamic of slurry-derived C and its consequences on soil CO2 efflux. Finally, 15N labelled slurries, supplemented or not with an additional C substrate, were used in a lysimeter study, under controlled conditions, to characterise the interactions between soil C and N processes post-organic fertilisation. Trailing-shoe application technique was shown to be and efficient way to lower NH3 volatilisation from land spread slurry. However, such benefice could be easily offset by an increase in direct N2O emissions and ecosystem respiration. Conversely, adjusting the timing of slurry spreading to get favourable soil and weather conditions, and to better meet herbage N requirements, had a positive effect on field N balance through a simultaneous reduction of both NH3 and N2O emissions. Emission factors (EF) calculated for slurry-induced N2O emissions were significantly lower than those calculated for mineral fertiliser and were greatly affected by weather and soil conditions. Such results support the widely spread idea of an inappropriate use of a single default EF value of 1% for both fertiliser types, under the IPCC Tier 1 methodology for national GHG inventories, and calls for the development of region-specific emission factors based on local soil types and climatic conditions.About 60% of slurry-derived C was shown to remain in the soil, even after 6 months, thus contributing to an increase of SOC pools. However, such incorporation of slurry-derived C may be offset by a positive priming effect of slurry on the degradation of the SOM. Such short-term priming of soil CO2 efflux may be, under certain conditions, compensated by a subsequent negative PE, thus minimising the impact of such phenomenon on the long-term sequestration of added slurry C. The long-term impact of these priming effects on nutrient and GHG balances remains to be further investigated, as these phenomena may occur on a regular basis in grassland ecosystems.